2017
DOI: 10.1111/jmft.12282
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sexual Communication in Couples’ Sexual Outcomes: A Dyadic Path Analysis

Abstract: In a study of 142 couples, we gathered survey data to show how sexual communication influences sexual and relationship satisfaction as well as sexual and orgasm frequency. In two dyadic data path analyses, we observed the significant paths of influence that sexual communication has on sexual and relationship satisfaction, as well as sexual and orgasm frequency. Our findings revealed greater amounts of sexual communication were associated with increased orgasm frequency in women and greater relationship and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 38 publications
1
44
2
2
Order By: Relevance
“…These results are especially compelling because this study was conducted in the Province of Quebec in Canada in which attitudes tend to be more liberal than in other parts of Canada or the United States (Hyde, DeLamater, & Byers, ). Thus, the prevalence of sexual problems and reduced sexual satisfaction may be even higher among clinical couples who hold more negative attitudes about sexuality or have more difficulty communicating about sex with their partner—both negative sexual attitudes and poor sexual communication are associated with lower sexual well‐being (Jones, Robinson, & Seedall, ; MacNeil & Byers, ; Mark & Jozkowski, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are especially compelling because this study was conducted in the Province of Quebec in Canada in which attitudes tend to be more liberal than in other parts of Canada or the United States (Hyde, DeLamater, & Byers, ). Thus, the prevalence of sexual problems and reduced sexual satisfaction may be even higher among clinical couples who hold more negative attitudes about sexuality or have more difficulty communicating about sex with their partner—both negative sexual attitudes and poor sexual communication are associated with lower sexual well‐being (Jones, Robinson, & Seedall, ; MacNeil & Byers, ; Mark & Jozkowski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that marital satisfaction in middle-aged couples who had high level of nontangible supports from adult children was high (30). Moreover, couples communication was found to affect their sexual satisfaction (31). This finding can be interpreted as follows: increased parenting-related stress , less time dedicated to each other due to the child's demands, greater engagement and reduced relationship between husband and wife, more parental responsibilities, and failure to divide the household chores and labor (32) which caused lower sexual and marital satisfaction at this stage of family life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that sexual dysfunction in these people and their disrupted ability to establish favorable and satisfactory sexual relationships with their partners reduce their self-confidence and desire for reestablishing a sexual relationship and gradually distance them from their spouse and reduce intimacy and affection in the couple. A reduced quality of sexual relationships can lead to sexual dysfunction in women with substance-dependent spouses and result in the women's loss of interest in expressing their sexual desires and ultimately cause a lower sexual assertiveness [27]. Other studies have also shown that women with substance-dependent husbands have problems in the phases of sexual desire, arousal and orgasm, experience a reduced frequency of sex, a transformed attitude toward sex and even a disgust with sex, and the women's interest in expressing their sexual priorities and needs to their spouse and thereby their sexual assertiveness diminish [7,15,16].…”
Section: Discussionmentioning
confidence: 99%